Lactose Variability of Escherichia coli in Thermally Stressed Reactor Effluent Waters - Kasweck, K. L. (1978)
Lactose-utilizing and nalidixic acid-resistant populations of Escherichia coli, having an optimum growth temperature of 37°C, were placed in modified diffusion chambers. The chambers were submerged in the epilimnion and hypolimnion of a 1,100-hectare lake (Par Pond) which receives cooling water from a nuclear production reactor. Control chambers were placed in a deep-water reservoir and a Flowing-Streams Laboratory, both of which had comparable temperatures to Par Pond. The populations of E. coli were sampled regularly for up to 3 weeks. Viability of the bacteria was determined by dilution plating to nutrient agar followed by replicate plating onto selective medium to determine lactose utilization and nalidixic acid sensitivity. Initial populations of E. coli were lactose positive but changed to lactose negative in Par Pond when the reactor was operating (i.e., cooling water from the heat exchangers was being discharged to the lake). This alteration occurred most rapidly in the chambers closest to the cooling-water discharge point. Such changes did not occur in a deep-water reservoir, in Par Pond when the reactor was not operating, or in the Flowing-Streams Laboratory. The nalidixic acid-resistant characteristic remained stable regardless of the chambers' placement or reactor operations. Although the reasons for such alterations are unclear, it appears that lactose-negative populations of E. coli are selected for in these reactor effluent waters. The loss of the lactose characteristic prevents the recognition and identification of E. coli in this cooling lake (when the reactor is operating) and may prevent the assessment of water quality based on coliform recognition.